Caminhos cruzados de Fanny Abramovich : a recepção da narrativa pelo leitor jovem - Magro, Maria Valquiria (2007)
The past few decades the studies in reading have increased. In this field, the several areas of knowledge articulate among themselves or, sometimes, isolate themselves with the purpose of shorten the distance between the teenager and the book, that has sharing space with DVD, media, electronic games and other attractive things of modern life. All the texts can instigate the reading, although the literary text, rich in fantasy necessary for the men, have characteristics that go beyond the pedagogical purpose: forms by the free capacity of involving the reader. It is in this context of realities and necessities that this dissertation was based on. Our objective was, starting in the Theory of Esthetic of Reception, proposed by Hans Robert Jauss, to observe the reception of the opus Cruzando Caminhos, by Fanny Abramovich, by the young reader, though his/her intrinsic abilities, the knowledge of world and his/her own expectations when facing the literary material. The group used in the research was composed by nine students, from 15 to 18 years old, residents of lower-middle class and high school students from public schools that, though questionnaires, registered aspects of their socio-economical situation and their reading impressions about the book mentioned. The answers of the questioned people and the opus of Fanny Abramovich, of Marisa Lajolo, of Regina Zilberman, of Hans Robert Jauss, of Ezequiel Theodoro da Silva, of Antonio Candido, of Robert Escarpit, among others, were used as a base for this research. The results of the research showed that the reading functions happened in part of the subjects of the research, reinforced in the way the narrative was built, which theme, characters and, specially, language, permitted the approach between the reader and the opus.